2020
DOI: 10.3389/fphar.2020.00211
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Use of Vitamin C in Cancer: Physiological Considerations

Abstract: Since the early studies of William J. McCormick in the 1950s, vitamin C has been proposed as a candidate for the treatment of cancer. A number of reports have shown that pharmacological concentrations of vitamin C selectively kill cancer cells in vitro and decrease the growth rates of a number of human tumor xenografts in immunodeficient mice. However, up to the date there is still doubt regarding this possible therapeutic role of vitamin C in cancer, mainly because high dose administration in cancer patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 63 publications
0
42
0
Order By: Relevance
“…Moreover, some reports have also demonstrated that vitamin C can inhibit growth of a number of human tumor xenografts in immunodeficient mice. In addition, some reports have also supported a chemopreventive action of vitamin C [33,34]. One of the relevant actions of vitamin C is its effect on cancer stem cells.…”
Section: Ascorbic Acidmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, some reports have also demonstrated that vitamin C can inhibit growth of a number of human tumor xenografts in immunodeficient mice. In addition, some reports have also supported a chemopreventive action of vitamin C [33,34]. One of the relevant actions of vitamin C is its effect on cancer stem cells.…”
Section: Ascorbic Acidmentioning
confidence: 98%
“…Moreover, vitamin C is an important contributor to immune defense of the body and has been found to be deficient in patients with advanced stages of cancer [33]. With independence of its mechanism of action, a large number of reports have shown that pharmacological concentrations of vitamin C can selectively kill cancer cells in vitro [34]. Moreover, some reports have also demonstrated that vitamin C can inhibit growth of a number of human tumor xenografts in immunodeficient mice.…”
Section: Ascorbic Acidmentioning
confidence: 99%
“…The essential characteristics of vitamin C (or ascorbic acid) and its potential usefulness against cancer, including PDAC, have recently been critically reviewed [ 195 ]. Humans cannot synthesize vitamin C, so it has to be consumed or taken as a supplement.…”
Section: Dietary Considerationsmentioning
confidence: 99%
“…Vitamin C has two main modes of action that could ultimately lead to anti-cancer effects. First, it is primarily an antioxidant that may reduce the risk of developing cancer by preventing oxidative damage to normal cells [ 195 ]. Second, in the specific presence of catalytic metals, such as iron and copper, vitamin C may become a pro-oxidant and behave as an anti-cancer agent, e.g., via production of H 2 O 2 [ 196 , 197 ].…”
Section: Dietary Considerationsmentioning
confidence: 99%
See 1 more Smart Citation